The use of translation theory through reconciling between Englishisation and translanguaging by Arab instructors in EMI higher education classes: Training postgraduate students to be translators and interpreters - Alwazna, Rafat Y. (Frontiers in Psychology, 2023)
Translation theory is taught at a postgraduate level in Arab countries through the use of English as a medium of instruction (EMI). It is often studied as a theoretical course, which is a major part of any EMI postgraduate translation/interpreting program taught in Arab universities. The present paper examines whether or not Arab instructors use translation theory when they train students in practical courses to be translators/interpreters in EMI higher education in a selection of Arabic-speaking countries in the Middle East. It also investigates whether or not translation theory, if used by Arab instructors in the translation/interpreting training at a postgraduate level, is utilized through English only or through translanguaging. It adopts a mixed method, consisting of a questionnaire, which has been distributed to 60 Arab translation/interpreting instructors/trainers from the selected Arab countries alongside three semi-structured interviews with three Arab professors who have been chosen from the 60 instructors for their long experience of translation/interpreting training. The paper argues that most of the participants use translation theory when training postgraduate students in practical courses to be translators/interpreters. This is because the use of theory offers students a solid ground for their problem-solving, decision-making and the ability to explain the logic behind their choice. The paper also shows that the participants do not completely adhere to English as a medium of instruction, rather they exercise translanguaging while using translation theory in practical courses. This is due to the specific translation/interpreting terminology contained in such theories, which may not be easily comprehended by students through the use of English on its own. Finally, the paper claims that the majority of the participants use multiple theories through translanguaging in their training. They argue that each theory has its own use and students should be exposed to as many theories as possible in EMI higher education in the selected Arab countries through translanguaging. This paper offers a baseline for using translation theory for the purpose of the translation/interpreting training through translanguaging in EMI higher education in the selected Arab countries, which may have implications for bilingual instruction of translation theory in other similar contexts.